In situ sequential STM imaging of structural changes resulting from the electrodissolution of silver crystal surfaces in aqueous perchloric acid : The roughening kinetics - Vela, María Elena (1996)
Structural changes of silver terrace domains in aqueous perchloric acid solution at constant anodic current density (j) and room temperature were followed by in situ scanning tunneling microscopy sequential imaging. For j<15 μA cm-2 silver electrodissolution proceeds at step edges without roughening. Conversely, for j<15 μA cm-2 the silver surface becomes progressively rougher to attain, after a certain critical time, a steady roughness. In this case, the dynamic scaling theory applied to STM images indicates that the dissolving silver surface can be described as a self-affine fractal surface with a static roughening exponent α50.9060.06, and a dynamic roughening exponent β50.3660.08. The value of a is consistent with the relevant role played by surface diffusion in the silver electrodissolution mechanism, whereas the value of b is slightly higher than those derived from growth models incorporating surface diffusion. The difference in the value of β would reflect the influence of either the electric field or energetic barriers at step edges on the rate of roughness development.